Health risk behaviours amongst school adolescents: protocol for a mixed methods study - Youness El Achhab; Abdelghaffar El Ammari; Hicham El Kazdouh; Adil Najdi; Mohamed Berraho; Nabil Tachfouti; Driss Lamri; Samira El Fakir; Chakib Nejjari (BMC, 2016)
Abstract Background Determining risky behaviours of adolescents provides valuable information for designing appropriate intervention programmes for advancing adolescent's health. However, these behaviours are not fully addressed by researchers in a comprehensive approach. We report the protocol of a mixed methods study designed to investigate the health risk behaviours of Moroccan adolescents with the goal of identifying suitable strategies to address their health concerns. Methods We used a sequential two-phase explanatory mixed method study design. The approach begins with the collection of quantitative data, followed by the collection of qualitative data to explain and enrich the quantitative findings. In the first phase, the global school-based student health survey (GSHS) was administered to 800 students who were between 14 and 19 years of age. The second phase engaged adolescents, parents and teachers in focus groups and assessed education documents to explore the level of coverage of health education in the programme learnt in the middle school. To obtain opinions about strategies to reduce Moroccan adolescents' health risk behaviours, a nominal group technique will be used. Discussion The findings of this mixed methods sequential explanatory study provide insights into the risk behaviours that need to be considered if intervention programmes and preventive strategies are to be designed to promote adolescent's health in the Moroccan school.